The Determinant of Stunting Prevalence in 24-59 Month Children in Hayahaya Village, Western Limboto Sub-district, Gorontalo Regency - Zakaria, Rabia; Suma, Juwita (Journal of Maternal and Child Health, 2020)
Background: Stunting is among the nutritional problems that lead to deficits in the children